Directive Illocutionary Act In Moana Movie - Ni Wayan Suastini; I Wayan Juniartha; Ayu Mas Wiliastini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
Directive is one type of illocutionary act usually used by the speaker to get the hearer to do something. This study discusses the types of directive illocutionary act found in Moana movie and followed by directive illocutionary act. This study used the theory by Kreidler (1998: 189-192) to discuss types of directive illocutionary act and used theory by Leech (1993: 104) to discuss the functions of directive illocutionary act. This study used the documentation method to collect the data and the method used in analyzing data was qualitative. In presenting the finding used formal and informal method. This study found 40 data of directive illocutionary act classified into 11 data or 27% of command, 15 data or 37,5% of request, 14 data or 35% of suggestion and all the data, including the directive function illocutionary act such as; competitive, convivial, collaborative, and conflictive. In the command type there are three functions that found based on the utterance which is collaborative, competitive, and conflictive. For the request type followed by four functions which are, competitive, convivial, collaborative and conflictive. The last type of directive illocutionary act is the suggestion, there are three functions also found in the utterance of Moana movie which is collaborative, convivial, and conflictive.